Tumor do glomo jugular Tumor of the glomus jugulare. A case report - Antonio Cesar G. Borges; Mario Ferreira Coutinho; Adão Anicet; Décio Lisboa Castro (Arquivos de Neuro-Psiquiatria)
É relatado um caso de tumor de glomo jugular com 4 anos de evolução. Os exames neuro-radiológicos mostraram destruição da pirâmide petrosa direita, deslocamento da cisterna pontocerebelosa direita e dilatação da cisterna ambiens do mesmo lado. O paciente foi submetido à cirurgia otológica, sendo o tumor removido parcialmente. Após radioterapia houve remissão parcial dos sintomas. A case of tumor of the glomus jugulare in a 57 years old patient in which the symptoms lasted four years is reported. The neuroradiological examination showed erosion of the petrous part of the right temporal bone, displacement of the right pontocerebellar cistern and dilatation of the ambiens cistern in the same side. The patient was submitted to otological surgery the tumor being partially removed. After the irradiation therapy some symptoms disappeared.